Perception and Modification: A Pragmatic Study of Irai Hyougen by Japanese Learners - Thamita Islami Indraswari; Wistri Meisa; Dian Rachmawati; Lintang Putri Ariyani (Universitas Diponegoro, 2021)
This research focused on describing how perceptions about the degree of imposition are manifested in requests in Japanese used by learners and how these perceptions are translated into choices of pragmatic modification. Through qualitative methods using the discourse completion test, it is known that perceptions of the degree of an imposition when requesting something are not manifested into the choice of request type used by learners. Instead, it is more visible from the variation in the choice of syntactic patterns used in request expression. The perception of the degree of imposition translated into a choice of external and internal pragmatic modifications. Although learners have varying perceptions of the degree of imposition for the same request, it does not appear that learners differentiate the choice of pragmatic modification based on the heaviness of the request’s imposition.